On-site detection of fish furunculosis by combining DNAzyme and carboxyl-functionalized graphene - Ding, Wen; Miao, Qingzhen; Bao, Xiuli; Wang, Shiyuan; Lu, Jing; Lyu, Mingsheng; Wang, Shujun (Frontiers in Chemistry, 2022)
Furunculosis, which is caused by Aeromonas salmonicida, can induce septicemia, leading to the rapid death of fishes belonging to Salmonidae, Cyprinidae, and Fuscheridae, and lamprey. Targeting A. salmonicida, five DNAzyme sequences with the highest enrichment rates were selected through the Systematic Evolution of Ligands by Exponential Enrichment (SELEX). The enrichment rates were 34.78, 23.60, 8.91, 2.89, and 2.34%, respectively. The DNAzyme with the highest activity, named D-AS-2, showed specificity and sensitivity. D-AS-2 was combined with carboxyl-functionalized graphene to construct a biosensor, which showed good fluorescence response to scabies lesion samples. The diagnostic procedure was completed in <2 min and can be used for the on-site diagnosis of fish diseases. A low-cost, rapid, simple, and highly specific biosensor for the diagnosis of furunculosis was established based on DNAzyme and carboxyl-functionalized graphene.